On latitudinal profile of Storm Sudden Commencement in H, Y and Z at Indian Geomagnetic Observatory chain - Rastogi, R.G.; Pathan, B.M.; Rao, D.R.K.; Sastry, T.S.; Sastri, J. H. (2001)
The unique network of geomagnetic observatories along 145°E geomagnetic longitude extending from the magnetic equator to the north pole has enabled to study the latitudinal profiles of Storm Sudden Commencement (SSC) amplitudes in the three components H, Y and Z of the geomagnetic field separately for the daytime and nighttime events. An abnormally large positive impulse of Z is observed at the equatorial stations with maximum at Trivandrum during the daytime as well as the night time hours suggesting large induced current within the earth’s crust south of Indian continent. The daytime enhancement of SSC (H) at the extended equatorial latitudes is undoubtedly due to the disturbed electric field generated by the magnetopause current communicated to the equator through polar latitudes. A prominent decrease of SSC (H) during night hours and the ‘induction vector’ at SSC frequencies at equatorial latitudes are indicative of the concentration of induced current from source fields extended in altitudes.